Discourse Elements in English Academic Discourse - Yulia Chubarova; Natalia Rezepova (National Research University Higher School of Economics, 2016)
This paper presents a study of discourse elements in spoken academic discourse - a lecture - and identifies their specificities. The study seeks to identify discourse elements in a wide body of research material; to study structural, functional and pragmatic features of discourse elements in terms of the implementation of the intentions of the speaker; to identify from the auditory analysis any prosodic features of discourse elements. Discourse elements are specifically defined from the point of view of their pragmatics: the intention of the speaker influences the language of the lecture and the way in which ideas are connected with words. The study on discourse elements included several stages. Research material consisted of audio recordings of Philology lectures to students studying English as a foreign language by three native speakers of English (General American standard of pronunciation), all of whom are professors at American colleges and universities. In total, 6 lectures were recorded; they formed a wide body of research material lasting 7 hours 33 minutes. This wide body of research material consisted of 2 306 linguistic facts, i.e. discourse elements in context. From these, 150 fragments containing various discourse elements were then chosen to form a narrow body of research material lasting 40 minutes. The phonetic research consisted of auditory analysis: dividing the fragments of discourses into syntagms; defining the boundaries of syntagms; specifying pitch movement, tone level and type of scale; using perceptual gradations of each prosodic feature, etc. Prosodic marking was carried out in accordance with the method of notation adopted at the Department of English Phonetics at Moscow State Teacher Training University (1997). Scaling enabled the classification and sorting of all the studied elements (discourse elements). The authors used the following types of scales: nominative, ordinal and interval. Structural analysis proved that discourse elements have different structure and may be one-word elements and predicative phrases S+P incorporated into the structure of the academic discourse. All discourse elements can be divided into two large groups - connecting elements (connectors) and pragmatic elements. The results of the research show that the studied elements differ structurally and can perform various functions. The functions of the discourse elements, their structure, intentions of the speaker and also their position in the phrase determine their prosodic features.